Panca Curiga as a Local Epistemological System in Interpreting Sundanese Cultural Texts - Budi Setiawan Gardapandawa; Selmabelle Garluisya Simbar Kencana (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2026)
In the era of modernization and digitalization, Sundanese cultural issues are often regarded as irrelevant in modern intellectual discourse, resulting in the marginalization of Sundanese cultural knowledge by the dominance of technology and globalization. This condition creates additional challenges for younger generations in preserving local culture, which is often treated as a complementary aspect rather than an essential component of cultural education. This study aims to explore and formulate Panca Curiga as a local epistemological system of the Sundanese. It also examines how this concept functions in interpreting Sundanese texts through five interpretative elements: silib, sindir, simbol, siloka, and sasmita. These elements represent different modes of meaning-making in Sundanese tradition, including metaphor, indirect criticism, symbolism, hypothetical expression, and emotional or intuitive signals. This research adopts a qualitative approach with a grounded theory design to construct an interpretative framework derived from Sundanese cultural practices and meanings embedded in Panca Curiga. Grounded theory was selected because this study does not seek to test an existing theory; rather, it aims to develop a conceptual understanding of how meaning is culturally constructed and interpreted within Sundanese tradition. The primary data sources include Sundanese cultural literature, interviews with Sundanese cultural figures, and cultural observations related to Panca Curiga. Data analysis was conducted through open coding, axial coding, and selective coding to generate categories and relationships that explain meaning-making processes in Sundanese cultural texts. The findings of this study reveal that Panca Curiga is an effective local epistemological system for interpreting multilayered meanings in Sundanese cultural texts. The five elements of Panca Curiga—silib, sindir, simbol, siloka, and sasmita—are shown to form a contextual and cultural reading pattern, unveiling the epistemological, ethical, historical, and spiritual dimensions within Sundanese tradition. This study makes a significant contribution to the fields of semiotics and hermeneutics, particularly within the context of Sundanese culture, by introducing Panca Curiga as a local epistemological framework that goes beyond a mere interpretative tool. The application of Panca Curiga opens space for multilayered interpretative learning, enhancing the understanding of both traditional and contemporary Sundanese texts. Moving forward, this research can serve as a foundation for developing a model of learning based on local cultural approaches.